Morphological anisotropy of shear failure surfaces of granite rock bridges - Guangming Luo; Shengwen Qi; Bowen Zheng; Wei Lu (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract Rock bridges are critical for the stability of rock masses and often experience shear failure under natural conditions. As a manifestation of the failure mechanisms of rock bridges, we investigate the morphology of failure surfaces created by direct shearing on granite rock bridges with varying initial persistence rates. The failure surfaces were scanned using a 3D laser scanner, and the roughness of the profiles was quantified with the Hurst exponent. To describe the morphological anisotropy, we introduced an isotropy index. Our results indicate that the failure surfaces display significant morphological anisotropy, featuring rougher profiles in the direction parallel to the shear for samples with initial persistence rates exceeding 20%. The morphological anisotropy diminishes with decreasing persistence rates and shows an initial decrease followed by a significant increase during the progressive failure of rock bridges. We suggest through the morphological characteristics of the failure surfaces that a large slip is necessary to develop the typical morphology of mature faults documented at outcrop scales.